End users' motivations as a key for the adoption of the home energy management system - Jarosław Kowalski; Bożena Ewa Matusiak (International Journal of Management and Economics, 2019)
Development of renewable energy means that there is a growing demand for technology that helps to manage and consume it in an optimal way, using more energy when it is produced on sunny/ windy days, preferably at the place of production, and avoiding long-distance transmission. This opens the field for solutions based on the Internet of Things (IoT) technologies, advanced demand management, and the concept of smart energy. The creation of a smart home energy management system (HEMS), which will help end users to manage the produced electricity, was the goal of the project entitled "e-balance - Balancing Energy Production and Consumption in Energy Efficient Smart Neighbourhoods". Research with potential users carried out within the project showed that the existence of such systems in the home environment redefines the concept of electricity, which becomes tangible and always present in sight. Users also expected that the system would significantly reduce their electricity bills, an expectation which is not always confirmed by economic simulations. This means that the final solution will have to take account of other types of motivation and engagement, e.g., environmental ones. The paper presents conclusions from quantitative and qualitative research conducted within the "e-balance" project in Poland, Portugal, and the Netherlands.
Keywords: O310; Q420; 650; Internet of Things; smart city; smart energy; energy flexibility; user motivation research